A novel connection between nucleotide and carbohydrate metabolism in mitochondria: sugar regulation of the Arabidopsis nucleoside diphosphate kinase 3a gene - Hammargren, Jenni; Rosenquist, Sara; Jansson, Christer; Knorpp, Carina (Plant cell reports, 2008)
Sugar metabolism is intricately connected with mitochondria through the conversion of sugars to ATP, and through the production of carbon skeletons that can be used in anabolic processes. Sugar molecules also take part in signalling cascades. In this study we investigated the impact of sucrose on the expression of the Arabidopsis thaliana Nucleoside Diphosphate Kinase gene family (NDPK, EC 2.7.4.6), focusing on NDPK3a , the product of which is located predominantly in mitochondria. Using quantitative PCR we show that the NDPK3a gene is subject to sucrose and glucose induction, while no other Arabidopsis NDPK gene are sucrose-inducible. The induction reaches a half-maximum after about 6 hours and is stable for at least 48 h. Sucrose and glucose inductions were found not to be affected by the presence of a hexokinase inhibitor, N -acetyl-glucosamine. Furthermore, turanose, a sucrose analogue that is not metabolised in plant cells, did not induce NDPK3a gene expression. An analysis of the NDPK3a gene revealed two WBOXHWISO1 boxes in the promoter region, elements that have previously been reported to be involved in sugar signalling in barley via the SUSIBA2 protein. SUSIBA2 belongs to the WRKY group of transcription factors. In this study we used two mutants containing T-DNA insertions in WRKY -genes, AtWrky4 and AtWrky34 , to investigate the possible involvement of WRKY transcription factors in the sugar induction of NDPK3a .